Essential cell biology - Bruce Alberts (Garland Science, 2013)
This is a concise introductory guide to asthma, the medicines used in its treatment, and the role of the pharmacist and other healthcare professionals in counselling patients on their illness, lifestyle and medicines. As with other titles in the series, "Asthma in Focus" discusses the drugs used to treat the disease, and describes how the pharmacist can get involved in counselling patients